Chapter 17 Visualization and Functional Analysis of Spindle Actin and Chromosome Segregation in Mammalian Oocytes - Mogessie, Binyam (Humana Press, 2019)
Chromosome segregation is conserved throughout eukaryotes. In most systems, it is solely driven by a spindle machinery that is assembled from microtubules. We have recently discovered that actin filaments that are embedded inside meiotic spindles (spindle actin) are needed for accurate chromosome segregation in mammalian oocytes. To understand the function of spindle actin in oocyte meiosis, we have developed high-resolution and super-resolution live and immunofluorescence microscopy assays that are described in this chapter